Pharmacokinetics of Sulfadoxine and Pyrimethamine for Intermittent Preventive Treatment of Malaria During Pregnancy and After Delivery. (9th June 2017) - de Kock, M; Tarning, J; Workman, L; Nyunt, MM; Adam, I; Barnes, KI; Denti, P
Abstract : Sulfadoxine/pyrimethamine is recommended for intermittent preventative treatment of malaria during pregnancy. Data from 98 women during pregnancy and 77 after delivery in four African countries were analyzed using nonlinear mixed‐effects modeling to characterize the effects of pregnancy, postpartum duration, and other covariates such as body weight and hematocrit on sulfadoxine/pyrimethamine pharmacokinetic properties. During pregnancy, clearance increased 3‐fold for sulfadoxine but decreased by 18% for pyrimethamine. Postpartum sulfadoxine clearance decreased gradually over 13 weeks. This finding, together with hematocrit‐based scaling of plasma to whole‐blood concentrations and allometric scaling of pharmacokinetics parameters with body weight, enabled site‐specific differences in the pharmacokinetic profiles to be reduced significantly but not eliminated. Further research is necessary to explain residual site‐specific differences and elucidate whether dose‐optimization, to address the 3‐fold increase in clearance of sulfadoxine in pregnant women, is necessary, viable, and safe with the current fixed dose combination of sulfadoxine/pyrimethamine.